2015
DOI: 10.1021/jacs.5b05694
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Peptide That Enhances Endosomal Escape of Delivered Proteins in Vitro and in Vivo

Abstract: ABSTRACT:The inefficient delivery of proteins into mammalian cells remains a major barrier to realizing the therapeutic potential of many proteins. We and others have previously shown that superpositively charged proteins are efficiently endocytosed and can bring associated proteins and nucleic acids into cells. The vast majority of cargo delivered in this manner, however, remains in endosomes and does not reach the cytosol. In this study we designed and implemented a screen to discover peptides that enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 47 publications
3
122
2
Order By: Relevance
“…Using a systematic approach, we then narrowed down the optimal EED composition to containing two indole rings or one indole ring and two phenyl groups in either a FWF or WW composition. Interestingly, Li et al identified a highly charged Aurein 1.2 peptide that enhances endosomal escape 5-fold29.…”
Section: Discussionmentioning
confidence: 99%
“…Using a systematic approach, we then narrowed down the optimal EED composition to containing two indole rings or one indole ring and two phenyl groups in either a FWF or WW composition. Interestingly, Li et al identified a highly charged Aurein 1.2 peptide that enhances endosomal escape 5-fold29.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the process of lysosomal degradation is the most probable basis for resistance and emphasizes the need for the discovery of novel endosomal escape enhancers [13,57,93]. As a result of lysosomal degradation, relatively high concentrations of the targeted toxin are usually needed for modest cytosolic or nuclear delivery, leading to severe side-effects also for off-target cells [94]. Consequently, to increase the therapeutic window for tumor targeted toxins, the efficacy of delivery has to be enhanced and the following characteristics should be fulfilled: low immunogenicity and toxicity, minimized unspecific off-target effects, high efficacy and specificity as well as ease of use and production [13,57,95].…”
Section: Endosomal Escape In Cell Culture Modelsmentioning
confidence: 99%
“…It also shows a moderate anti-cancer activity on 52 out of the 54 cancer cells in the NCI testing program, at the concentrations that can kill bacterial and cancer cells without harming mammalian cells 2 . Even more interestingly, it substantially enhances the endosomal escape of protein when conjugated with a cargo cationic protein 4 . This short yet effective membrane-active peptide is of great interest for a better understanding of the interaction between antimicrobial peptides and membranes.…”
Section: Introductionmentioning
confidence: 99%